Influência das barragens nas seções fluviais a jusante de reservatórios em rios tropicais da zona de transição Cerrado Brasileiro-Amazônia - Martins, Bruno Silva (2021)
Hydroelectric plants are today the main source of electricity generation in Brazil. The construction of a dam and formation of a reservoir always disturb the natural conditions of a watercourse. Reservoirs retain the influent sediments due to the reduction in current velocity. According to the “hungry rivers” theory, to compensate for the loss in sediment, rivers can start digging their own channels downstream of the reservoir. We studied 6 cases of dams/reservoirs in the Cerrado-Amazon transition zone in order to verify whether the installation of the dam modifies the morphology of the channels downstream of the dam due to erosion caused by changes in the flow dynamics in the channel. For this purpose, the bathymetry, velocity and suspended sediments in sections of river channel downstream and upstream of two dams were surveyed in the field. Secondary data of the same parameters in 4 other dams in this zone were also obtained. No consistent reductions in suspended sediments or water velocity were observed in the downstream sections of dams after their construction. However, most of the watercourses of the evaluated HPPs showed erosion of the sections of channels downstream of the dam. These results suggest that the construction of hydroelectric dams did not always cause erosion downstream of the dams under study and that this phenomenon was not clearly associated with a reduction in suspended load or a change in the velocity of the water downstream of the dam.